Neuropathology of epilepsy: epilepsy-related deaths and SUDEP. Issue 1 (January 2019) - Thom, Maria
Abstract: Most pathologists will encounter deaths in patients with epilepsy in their practice, including sudden deaths. A systematic approach to these post-mortem examinations is required, including gathering relevant clinical details and around the circumstances of death, in order to correctly categorise these cases. Macroscopic and histological examination of the brain can reveal (i) the underlying cause of the epilepsy, as cortical dysplasia or tumours, (ii) sequel of previous seizures, including hippocampal sclerosis and contusions and (iii) potentially the cause of death. Sudden and unexpected death in epilepsy (SUDEP) is still under-reported as a cause of death. Although by definition there is no structural or toxicological cause of death at post-mortem, clinical and experimental studies together with neuropathological findings are beginning to identify alterations in central autonomic regions, including the brainstem, critical for cardio-respiratory regulation. Neuropathology investigations following post-mortem examinations form an essential component in the identification of disease mechanisms in epilepsy-related deaths and their future prevention.